Structured films and optical articles including structured films

JP2024502733A5Pending Publication Date: 2024-12-233M INNOVATIVE PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023536852
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-18
Filing Date
2021-12-15
Publication Date
2024-12-23

AI Technical Summary

Technical Problem

Conventional lithographic patterning processes for creating nanostructured articles are complex and inefficient, particularly when scaling up to larger formats, and they do not effectively integrate structured films with waveguides for optical applications without additional sequential steps.

Method used

A method for applying structured films, such as nanostructures, onto substrates without the sequential steps of typical lithographic patterning processes, using a continuous roll-to-roll process to create structured films larger than conventional formats, and integrating these films with waveguides by bonding them using a planarizing backfill layer and adhesive layer with controlled refractive index differences and surface roughness.

Benefits of technology

Enables the efficient production of structured films that can be seamlessly integrated with waveguides, reducing complexity and cost while maintaining optical functionality, suitable for applications like optical metasurfaces and augmented reality waveguides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The optical article includes a waveguide and a structured film. The structured film includes a polymer substrate, an etch stop layer disposed on the polymer substrate, a structured layer including a plurality of textured structures disposed on a side of the etch stop layer opposite the polymer substrate, a planarizing backfill layer disposed on the plurality of textured structures, the planarizing backfill layer defining a substantially planar major surface of the planarizing backfill layer having a surface roughness Ra, and an adhesive layer disposed on the substantially planar surface of the planarizing backfill layer and bonding the structured film to the waveguide. The difference in refractive index between the planarizing backfill layer and the structured layer is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm. The adhesive layer has an average thickness ta and a surface roughness Ra of at least 0.25. <ta<(1 / 4)W1である。
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Structured articles, such as nanostructured articles, are useful in a variety of applications, including optical applications, such as optical metasurface applications. Summary of the Invention

[0002] FIELD OF THE DISCLOSURE This specification relates generally to structured films and optical articles including structured films.

[0003] In some embodiments of the present disclosure, an optical article is provided. The optical article includes a waveguide and a structured film. The structured film includes a polymer substrate, an etch stop layer disposed on the polymer substrate, a structured layer including a plurality of engineered structures disposed on a side of the etch stop layer opposite the polymer substrate, a planarizing backfill layer disposed on the plurality of engineered structures, the planarizing backfill layer defining a substantially planar main surface of the planarizing backfill layer having a surface roughness Ra, and an adhesive layer disposed on the substantially planar main surface of the planarizing backfill layer and bonding the structured film to the waveguide. The difference in refractive index between the planarizing backfill layer and the structured layer is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm. The adhesive layer has an average thickness ta and a surface roughness Ra of at least 0.25. <ta<(1 / 4)W1である。

[0004] In some aspects of the present specification, a structured film is provided. The structured film includes a polymer substrate, an etch stop layer disposed on the polymer substrate, a structured layer including a plurality of processed structures disposed on a side of the etch stop layer opposite to the polymer substrate, and a planarizing backfill layer disposed on the plurality of processed structures, the planarizing backfill layer defining a substantially flat main surface having a surface roughness Ra, and an adhesive layer disposed on the substantially flat main surface of the planarizing backfill layer. The processed structures can be inclined with respect to the etch stop layer. The difference in refractive index between the planarizing backfill layer and the structured layer is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm. The adhesive layer has an average thickness ta, and Ra < ta < (1 / 4)W1.

[0005] In some aspects of the present specification, an optical article is provided that includes a waveguide and a structured film disposed on a main surface of the waveguide. The structured film includes an etch stop layer, a structured layer disposed on the etch stop layer and including a plurality of processed structures, and a planarizing backfill layer disposed on the plurality of processed structures, the planarizing backfill layer defining a substantially unstructured main surface having a surface roughness Ra, and an adhesive layer disposed on the substantially unstructured main surface of the planarizing backfill layer. The difference in refractive index between the planarizing backfill layer and the structured layer is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm. The adhesive layer joins the structured film to the main surface of the waveguide and has an average thickness ta such that Ra < ta < (1 / 4)W1. The processed structures can be inclined with respect to the etch stop layer.

[0006] In some aspects of this specification, a structured film is provided. The structured film includes a polymer substrate, an etch stop layer, a dynamic separation layer disposed between the polymer substrate and the etch stop layer, a structured layer including a plurality of processed structures disposed on a side of the etch stop layer opposite the dynamic separation layer, a planarizing backfill layer disposed on the plurality of processed structures and defining a substantially flat main surface of the planarizing backfill layer having a surface roughness Ra, and an adhesive layer disposed on the substantially flat main surface of the planarizing backfill layer. The difference in refractive index between the planarizing backfill layer and the structured layer is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm. The adhesive layer has an average thickness ta, and Ra < ta < (1 / 4)W1. The dynamic separation layer is adapted to facilitate separation of the polymer substrate and the etch stop layer upon activation.

[0007] These and other aspects will become apparent from the following detailed description. However, in no case should this brief summary be construed as limiting the subject matter of the claims.

Brief Description of the Drawings

[0008] [Figure 1] FIG. is a schematic cross-sectional view of an optical article including a waveguide and a structured film including a polymer substrate according to some embodiments. [Diagram 2] FIG. is a schematic cross-sectional view of an optical article including a waveguide and a structured film including a polymer substrate according to some embodiments. [Diagram 3] FIG. is a schematic cross-sectional view of an optical article including a waveguide and a structured film including a polymer substrate according to some embodiments. [Figure 4A] FIG. schematically shows removing a polymer substrate from an optical article according to some embodiments. [Figure 4B] FIG. schematically shows removing a polymer substrate from an optical article according to some embodiments. [Figure 5A]1A-1C are schematic diagrams illustrating the removal of a polymer substrate from an optical article including a separation layer according to some embodiments. [Figure 5B] 1A-1C are schematic diagrams illustrating the removal of a polymer substrate from an optical article including a separation layer according to some embodiments. [Figure 5C] 1A-1C are schematic diagrams illustrating the removal of a polymer substrate from an optical article including a separation layer according to some embodiments. [Figure 6A] 1 is a schematic cross-sectional view of an optical article including a waveguide and a structured film including a gradient structure according to some embodiments. [Figure 6B] 1 is a schematic cross-sectional view of an optical article including a waveguide and a structured film including a gradient structure according to some embodiments. [Figure 6C] 1 is a schematic cross-sectional view of an optical article including a waveguide and a structured film including a gradient structure according to some embodiments. [Figure 7A] FIG. 1A-C are schematic diagrams illustrating a process for making a structured film, according to some embodiments. [Figure 7B] FIG. 1A-C are schematic diagrams illustrating a process for making a structured film, according to some embodiments. [Figure 7C] FIG. 1A-C are schematic diagrams illustrating a process for making a structured film, according to some embodiments. [Figure 8] 1 is a schematic cross-sectional view illustrating light incident on one or more layers according to some embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In the following description, reference is made to the accompanying drawings, which form a part hereof, and in which various embodiments are shown by way of illustration. The drawings are not necessarily to scale. It is to be understood that other embodiments are contemplated and may be made without departing from the scope or spirit of the present disclosure. Accordingly, the following detailed description is not to be taken in a limiting sense.

[0010] Nanostructured articles can be formed by patterning functional materials. Patterning of functional materials can be performed by depositing a uniform layer of functional material on a substrate (e.g., a waveguide) and then forming a pattern in the material using a lithographic patterning process. Other methods of forming nanostructured articles are described, for example, in WO 2020 / 095258 (Van Lengerich et al.) and WO 2020 / 097319 (Wolk et al.).

[0011] According to some embodiments herein, structured films are provided that can be used to apply structures (e.g., nanostructures) onto a substrate without the sequence of steps used in typical lithographic patterning processes. The structured films can be substantially larger than, for example, semiconductor wafer formats used in conventional nanoimprint lithography (NIL) batch processes, or display glass substrates typically used in large-scale NIL or roll-to-plate NIL. In some embodiments, the structured films have maximum dimensions of, for example, greater than 100 mm, 200 mm, 300 mm, 450 mm, or 600 nm. In some embodiments, the structured films have maximum dimensions of, for example, greater than 4 m, or greater than 5 m, or greater than 10 m, or greater than 50 m, or greater than 100 m. The structured films can be made in a continuous roll-to-roll process. In some embodiments, rolls of structured films are provided. In some embodiments, the rolls are converted into sheets.

[0012] For example, the structured film may include a low refractive index layer separating the structured layer from the polymer substrate, or the polymer substrate included in the structured film may be removed after the structured film is applied to the waveguide. The structured film may be designed to create the equivalent of a surface relief grating (SRG) or optical metasurface on the waveguide, for example, without the series of lithographic patterning steps utilized in typical SRG patterning processes.

[0013] Figures 1 to 3 are schematic cross-sectional views of optical articles 100, 200, and 300, respectively. In some embodiments, the optical article 100 (200, 300, respectively) includes a waveguide 190 and a structured film 150 (250, 350, respectively). The structured film 150 (250, 350, respectively) includes a polymer substrate 130, an etch stop layer 137 disposed on the polymer substrate 130, and a structured layer 110 (210, 310, respectively) including a plurality of processed structures 129 (229, 329, respectively) disposed on a side of the etch stop layer 137 opposite the polymer substrate 130, and a planarization backfill layer 115 (215, 315, respectively) disposed on the plurality of processed structures 129 (229, 329, respectively) to define a substantially flat main surface 121 (221, 321, respectively), the planarization backfill layer 115 (215, 315, respectively) having a surface roughness Ra (see, for example, FIGS. 7A to 7C), and an adhesive layer 140 disposed on the substantially flat main surface 121 (221, 321, respectively) of the planarization backfill layer 115 (215, 315, respectively) to bond the structured film to the waveguide 190. The difference in refractive index between the planarization backfill layer 115 (215, 315, respectively) and the structured layer can be at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm or other ranges described elsewhere in this specification. The adhesive layer 140 has an average thickness ta, and Ra < ta < (1 / 4)W1. The surface roughness Ra is the average deviation surface roughness. The surface roughness Ra can be determined, for example, in accordance with the ISO 4287:1997 standard specification.

[0014] A major surface 121 (221, 321, respectively) can be considered substantially planar if any deviation from planarity in a lateral (e.g., xy-plane) length scale substantially greater than the average height t2 (e.g., 100 times t2 or 1000 times t2) is substantially less than the average height t2 (e.g., less than 20%, or less than 10%, or less than 5%, or less than 3% of the average height t2). In some embodiments, a substantially planarized surface has a planarization amount (P) of more than 50%, more preferably more than 75%, and most preferably more than 90%, where the planarization amount is given by P=(1-(a1 / a2))×100%, where a1 is the relief height of a surface layer (e.g., a planarized backfill layer) and a2 is the feature height of the features covered by the surface layer, as further disclosed in P. Chiniwalla, IEEE Trans. Adv. Packaging 24(1), 2001, 41.

[0015] The adhesive layer 140 can have an average thickness in a range suitable for a given application. In some embodiments, the average thickness ta of the layer 140 is less than 250 nm, or less than 200 nm, or less than 150 nm, or less than 100 nm, or less than 75 nm, or less than 50 nm, or less than 40 nm, or less than 30 nm. In some such embodiments, or in other embodiments, the average thickness ta is at least 5 nm, or at least 10 nm, or at least 15 nm. In some embodiments, the average thickness ta is selected to be less than 1 / 4 of the wavelength of interest. For example, for visible light, it may be preferred that the average thickness is less than 100 nm or substantially less than 100 nm (e.g., less than 50 nm), while for near-infrared light, the average thickness may be, for example, up to 250 nm, or even greater if longer wavelengths are of interest. Having a thickness less than 1 / 4 of the wavelength of interest allows, for example, the resulting structures formed in one or more unstructured layers to couple to evanescent waves in a waveguide. This can allow the resulting structure to be used, for example, as a surface relief grating (SRG). SRG, as used herein, includes cases where the grating is embedded in a material with a different refractive index. The structure can be used, for example, for optical incoupling and / or outcoupling (e.g., to an augmented reality waveguide element). Alternatively or in addition, the resulting structure may be used as a light distribution element, an orthogonal pupil expander, or a redirection element, for example, for exit pupil expansion in an augmented reality waveguide element. Illustrative examples of the use of SRGs in image-preserving waveguides can be found, for example, in WO 2019 / 195186 (Peroz et al.).

[0016] Layer 140 may be a polymeric or monomeric adhesive layer and / or an optically clear adhesive layer. Suitable optically clear adhesives include those available, for example, from Norland Products, Inc. (Cranbury, NJ). Other suitable adhesives include thermosetting materials, such as those available under the trade name CYCLOTENE from Dow Chemical Company (Midland, MI). Still other suitable adhesives include heat-activated adhesives, such as those available under the trade name KRATON from KRATON Polymers (Huston, TX). Suitable adhesive layers, including thin adhesive layers (e.g., less than 50 nm thick), are described, for example, in U.S. Pat. Nos. 7,521,727 (Khanarian et al.), 7,53,419 (Camras et al.), 6,709,883 (Yang et al.), and 6,682,950 (Yang et al.).

[0017] The polymer substrate 130 may be, for example, a polyethylene terephthalate (PET) film or a polycarbonate film, and may be dimensionally stabilized (e.g., heat set). Other suitable materials for the polymer substrate 130 include, for example, other polyesters or copolyesters, polyurethanes, polymethylmethacrylates, polystyrenes, polyimides, polyethylene naphthalates, polypropylenes, and cyclic olefin copolymers. In some embodiments, the polymer substrate has low birefringence (the maximum in-plane difference in refractive index at the first wavelength W1 multiplied by the layer thickness). In some embodiments, the retardance is less than 50 nm, or less than 10 nm, or less than 5 nm, or less than 1 nm.

[0018] The waveguide 190 may be, for example, a glass waveguide or a polymer (e.g., polymethylmethacrylate) waveguide. In some embodiments, the waveguide 190 is, for example, an image-preserving waveguide (e.g., a waveguide such that when light containing an image (e.g., light from a display) propagates along the waveguide and is then coupled out of the waveguide, the coupled light retains the image). In some embodiments, the waveguide combiner includes a waveguide and a structured film structure that defines an optical metasurface input and / or output coupler. Waveguide combiners are described, for example, in Kress, “Optical waveguide combiners for AR headsets: features and limitations”, Proc. SPIE 11062, Digital Optical Technologies 2019, 110620J (16 July 2019); doi:10.1117 / 12.2527680.

[0019] In some embodiments, the engineered structures 129 have a length and a width in orthogonal directions (e.g., x and y directions), each orthogonal to the thickness direction (z direction). In some embodiments, the plurality of engineered structures 129 (229, 329, respectively) are or include a plurality of nanostructures. Nanostructures are structures having at least two orthogonal dimensions (e.g., at least two of height, length, and width) in the range of about 1 nm to about 1000 nm. Engineered structures are structures that are purposely fabricated with a predetermined geometric shape (e.g., a predetermined length, width, and height). Some representative shapes of engineered structures (e.g., engineered nanostructures) include, but are not limited to, rectangular, triangular, and trapezoidal prisms, fins, cylindrical and truncated conical pillars, and other such shapes. In some embodiments, the engineered structures have an average aspect ratio (height divided by length or width or largest lateral (orthogonal to height) dimension) of, for example, at least 0.1, or at least 0.2, or at least 0.5, or at least 1, or at least 2, or at least 5, or at least 10. The engineered structures can be arranged with a regular or irregular (e.g., pseudo-random distribution where the structures appear to be randomly arranged but are created from an underlying deterministic process), pitch, orientation, and / or shape, in some cases depending on the functionality and manufacturability of the application.

[0020] In some embodiments, the planarizing backfill layer 115 (215, 315, respectively) includes a residual layer 142 (242, 342, respectively) between the adhesive layer 140 and the structured layer 110 (210, 320, respectively). The residual layer can be described as the portion of the backfill layer above the top of the structures (in the positive z-direction) of the structured layer. In some embodiments, the ratio of the average (unweighted average) thickness t1 of the residual layer 142 to the average height t2 of the plurality of processed structures is less than 1, or less than 0.5, or less than 0.3, or less than 0.25. In some embodiments, t1 / t2 is in the range of 0.001 to 0.5, for example. In some embodiments, the maximum thickness (t1+t2) of the planarizing backfill layer is 2 times or less, or 1.5 times or less, or 1.3 times or less than the average height t2 of the plurality of processed structures. In some embodiments, the thickness of the residual layer 142 is less than 100 nm, less than 50 nm, less than 30 nm, less than 20 nm, or less than 10 nm.

[0021] A major surface 121 (respectively 221, 321) may be considered substantially unstructured if any structures that may be present on that surface have a height that is substantially less than the average height t2 (e.g., less than 20%, or less than 10%, or less than 5%, or less than 3% of the average height t2). A major surface 121 (respectively 221, 321) may be considered substantially planar if any deviation from planarity on a lateral (e.g., xy-plane) length scale that is substantially greater than the average height t2 (e.g., 100 times t2 or 1000 times t2) is substantially less than the average height t2 (e.g., less than 20%, or less than 10%, or less than 5%, or less than 3% of the average height t2).

[0022] In some embodiments, the polymer substrate 130 is releasably attached to an etch stop layer 137 and is removed after the structured film is bonded to the waveguide (see, e.g., FIGS. 4A-6C). Alternatively, in some embodiments, after the structured film is bonded to the waveguide, the polymer substrate 130 is removed by dissolving the layer in acid. In either case, after the polymer substrate 130 is removed, the etch stop layer 137 may optionally be removed, for example, by reactive ion etching.

[0023] Two layers are releasably attached to each other when they can be separated from each other with little or no damage to either layer (e.g., the damage is small enough that it is not easily visible to the naked eye of a person with normal vision). A first layer and a second layer are releasably attached to each other includes a third layer disposed between the first layer and the second layer, the third layer adapted to facilitate separation of the first layer and the second layer (e.g., the third layer may be adapted to split or be separated from at least one of the first layer and the second layer). The third layer may be adapted to facilitate separation of the first layer and the second layer only after activation of the third layer (e.g., by irradiation or chemical activation, or thermal activation). For example, the third layer may be a dynamic separation layer. A dynamic separation layer is a layer that can be changed from a first state to at least a second state (e.g., by activating the separation layer with irradiation), where in the first state the layer provides higher adhesion to at least one adjacent layer, and in the second state the layer provides lower adhesion to at least one adjacent layer. For example, the dynamic separation layer can be a light-induced stress mode peeling layer (e.g., a polymer layer that can be crosslinked or further crosslinked upon irradiation such that increased crosslinking generates stress that promotes peeling from adjacent layers), and / or a light-to-heat conversion (LTHC) layer.

[0024] The structured film can be configured such that the polymer substrate 130 is peelably attached to the etch stop layer 137 by including a split layer between the polymer substrate 130 and the etch stop layer 137, or by including a dynamic separation layer between the polymer substrate 130 and the etch stop layer 137 and activating the dynamic separation layer (e.g., by irradiation). The split layer can be a static separation layer, which can be, for example, a low surface energy layer, or a layer coextruded with and weakly adhered to the polymer substrate 130 (e.g., separation layer 160' shown in FIG. 5A according to some embodiments), as generally described, for example, in U.S. Pat. No. 9,415,561 (Lindquist et al.). The dynamic separation layer (e.g., LTHC layer) can include multiple sublayers. Suitable dynamic separation layers include carbon black nanocomposites, thin light-absorbing metal (e.g., aluminum, titanium, or chromium) layers, and light-absorbing optical cavities such as those defined by thin (e.g., 10-30 nm) metal (e.g., aluminum, titanium, or chromium) layers separated by polymer layers such as acrylate layers. The dynamic separation layer can be formed, for example, from 3M Light-To-Heat Conversion Release Coating (LTHC) Ink (available from 3M Company, St. Paul, MN). Other suitable dynamic separation layers include LTHC layers as described, for example, in U.S. Pat. Nos. 7,977,864 (Bellmann et al.) and 7,670,450 (Lamansky et al.).

[0025] In some embodiments, an additional layer 160 is disposed between the etch stop layer 137 and the polymer substrate 130. This is shown, for example, diagrammatically in FIG. 2 for structured film 250, which may correspond to structured film 150, except for the additional layer 160. Similarly, an additional layer 160 may be optionally included between the etch stop layer 137 and the polymer substrate 130 of structured film 350 of FIG. 3. The additional layer 160 may be, for example, a low refractive index layer, or a dividing or separating layer. In some embodiments, the additional layer 160 is a dynamic separation layer (e.g., a light-to-heat conversion (LTHC) layer) disposed between the etch stop layer 137 and the polymer substrate 130. In some such embodiments, an additional polymer layer is disposed between the etch stop layer 137 and layer 160 (see, for example, FIGS. 5B-5C). In some embodiments, a dynamic separation layer is included, with a low refractive index layer between the dynamic separation layer and the etch stop layer 137. In some embodiments, the dynamic separation layer 160 is adapted to facilitate separation of the polymer substrate and the etch stop layer upon activation. Activation can be achieved, for example, by irradiation. Suitable radiation may include one or more wavelengths, including visible, infrared, or ultraviolet light from a laser, lamp, or other radiation source. Useful irradiation conditions are described, for example, in U.S. Patent No. 7,977,864 (Bellmann et al.).

[0026] 4A-5C illustrate various methods of removing polymer substrate 130. In FIGS. 4A-4B, optical articles 100′ and 100″ may correspond to optical article 100, for example. Optical article 100′ is configured such that polymer substrate 130 is releasably attached to etch stop layer 137. In this and some other embodiments, there is a split interface between polymer substrate 130 and etch stop layer 137, which may result from a surface treatment applied to polymer substrate 130 prior to applying etch stop layer 137 to polymer substrate 130. Optical article 100″ is configured such that etch stop layer 137 is releasably attached to layers 110 and 115. In this and some other embodiments, there is a split interface between etch stop layer 137 and layers 110 and 115, which may result from a surface treatment applied to etch stop layer 137 prior to disposing layer 110′ (see FIG. 7A ) on etch stop layer 137, for example.

[0027] In FIGS. 5A-5C, optical articles 200′ and 200″ may correspond to, for example, optical article 200. In FIG. 5A, the polymer substrate is releasably attached to a separation layer 160′, which may be a static separation layer (e.g., coextruded with polymer substrate 130) or a dynamic separation layer. In this and some other embodiments, a split interface exists between polymer substrate 130 and separation layer 160′, which may result from coextrusion of polymer substrate 130 and separation layer 160′, for example, as generally described in U.S. Pat. No. 9,415,561 (Lindquist et al.). In FIG. 5B, dynamic separation layer 160″ is disposed between polymer substrate 130 and etch stop layer 137. Additional substrate layer 132 is disposed between dynamic separation layer 160″ and etch stop layer 137. Additional substrate layer 132 may be, for example, a low refractive index layer (e.g., having a refractive index in the ranges described elsewhere herein for low refractive index layers). The dynamic separation layer 160'' may be adapted to be releasably attached to the additional substrate layer 132 upon activation. In this and some other embodiments, upon activation, a split interface exists between the dynamic separation layer 160'' and the additional substrate layer 132, as shown generally in FIG. 5C.

[0028] In some embodiments, the structured film 250 includes a polymer substrate 130, an etch stop layer 137, a dynamic separation layer 160 disposed between the polymer substrate and the etch stop layer, a structured layer 210 including a plurality of processed structures 229 disposed on a side of the etch stop layer 137 opposite the dynamic separation layer 160, a planarizing backfill layer 215 disposed on the plurality of processed structures 229, the planarizing backfill layer 215 defining a substantially planar major surface 221 of the planarizing backfill layer 215 having a surface roughness Ra, and an adhesive layer 140 having an average thickness ta disposed on the substantially planar major surface 221 of the planarizing backfill layer 215. In some embodiments, the dynamic separation layer is adapted to facilitate separation of the polymer substrate 130 and the etch stop layer 137 upon activation (e.g., by irradiation). For example, the dynamic separation layer 160 may be adapted to peel from the etch stop layer 137 upon activation (e.g., by irradiation), or the dynamic separation layer 160 may be adapted to peel from an additional layer (see, e.g., FIG. 5C) disposed between the etch stop layer 137 and the dynamic separation layer upon activation. In some embodiments, the difference in refractive index between the planarizing backfill layer 215 and the structured layer 210 is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm, or other ranges described elsewhere herein. In some embodiments, Ra <ta<(1 / 4)W1である。

[0029] In some embodiments, it is desired to retain the polymer substrate 130 within the structured film. However, in some cases, it is desirable to have a layer (e.g., air or a low index cladding layer) adjacent to the etch stop layer 137 that has a lower index of refraction than the polymer substrate 130. Such a layer can be included to improve planarization backfill and light confinement in the structured layer. In some embodiments, the additional layer 160 is a low index unstructured layer. Suitable low index layers include, for example, nanoporous coatings, xerogels and aerogels, perfluoropolyethers, TEFLON, CYTOP materials, hexafluoropropylene oxide (HFPO), or fluorenol methacrylate. Useful low index layers are described, for example, in U.S. Pat. No. 8,808,811 (B Kolb et al.). In some embodiments, the additional layer 160 is a fluoropolymer layer. The low index layer can have an index of refraction, for example, in the range of 1.1 to 1.45, or 1.15 to 1.4, or 1.2 to 1.35, for at least the first wavelength W1. In some embodiments, the low index layer has a thickness of, for example, at least 50 nm, or at least 100 nm, or at least twice t2, or at least 5 times t2. In some such embodiments, or in other embodiments, the low index layer has a thickness of, for example, 10 micrometers or less, or 5 micrometers or less. In some embodiments, the structured film 250 includes an unstructured layer 160 disposed between the etch stop layer 137 and the polymeric substrate 130, where the difference in refractive index between the planarizing backfill layer 215 and the unstructured layer 160 is at least 0.2, or at least 0.25, for at least the first wavelength W1.

[0030] In some embodiments, the processed structures 129 or 229 are inclined relative to the etch stop layer 137. Figure 3 is a schematic cross-sectional view of an article 300 including a structured film 350 having a processed structure 329 inclined relative to the etch stop layer 137. In some embodiments, the structured film 350 includes a polymer substrate 130, an etch stop layer 137 disposed on the polymer substrate 130, a structured layer 310 including a plurality of processed structures 329 disposed on a side of the etch stop layer 137 opposite the polymer substrate 130, the processed structures 329 being inclined relative to the etch stop layer 137, a planarizing backfill layer 315 disposed on the plurality of processed structures 329 and defining a substantially planar major surface 321 having a surface roughness Ra, and an adhesive layer 140 having an average thickness ta disposed on the substantially planar major surface of the planarizing backfill layer. In some embodiments, the difference in refractive index between the planarizing backfill layer 315 and the structured layer 310 is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm, or other ranges described elsewhere herein. <ta<(1 / 4)W1である。

[0031] An engineered structure is tilted if a line passing through the center of the top (facing away from the etch stop layer 137) and bottom (facing towards the etch stop layer 137) of the structure makes an angle in the range of 5 to 85 degrees with respect to the etch stop layer 137. For top and bottom facets, the center can be the centroid of the top and bottom of the structure. For example, engineered structure 329 can be said to be tilted if a line 341 passing through the centroid of facet 343 of the engineered structure facing towards the etch stop layer 137 and through the centroid of the opposite facet 346 facing away from the etch stop layer 137, or through that point in the case of a pointed engineered structure, makes an angle θ0 in the range of 5 to 85 degrees with respect to the etch stop layer 137. A tilted engineered structure can have opposing sidewalls that make angles θ1 and θ2 with respect to the etch stop layer 137. The angles θ1 and θ2 are exterior angles (angles on the outside of the structure 329). The angle θ0 and / or the angle θ1 may be, for example, at least 45 degrees, or at least 50 degrees, and / or may be, for example, 85 degrees or less, or 80 degrees or less, or 75 degrees or less. In some embodiments, the angle θ0 and / or the angle θ1 may be, for example, in a range of 45-85 degrees or 50-80 degrees. The angle θ2 may be about 180 degrees minus θ1, or may be different. In some embodiments, the angle θ2 may be, for example, in a range of 95 degrees to 135 degrees. In some embodiments, for at least a majority (or at least 60%, or at least 80%, or at least 90%) of the processed structures, each processed structure has a sidewall that defines an exterior angle θ1 with respect to the etch stop layer 137 in a range of 45 degrees to 85 degrees. The structured layer 310 may optionally include non-sloped structures in addition to the sloped processed structures 329. In some embodiments, at least 60%, or at least 80%, or at least 90% of all features defined in structured layer 310 are tilted relative to etch stop layer 137 .

[0032] In some embodiments, after structured film 150, 250, or 350 is bonded to a waveguide, polymer substrate 130 is removed. Figures 6A-6C are schematic cross-sectional views of exemplary articles that can be formed by bonding a structured film to a waveguide 190 and then removing polymer substrate 130. Figure 6A shows a schematic of structured film 351 that can be formed from structured film 350 by removing polymer substrate 130. Similarly, structured films can be obtained from structured films 150 and 250 by removing polymer substrate 130 and, optionally, additional layer 160 of structured film 250.

[0033] In some embodiments, optical article 301 (or 301 ′, 301 ″ shown in FIGS. 6B-6C) includes waveguide 190 and structured film 351 disposed on major surface 191 of waveguide 190 . The structured film 351 includes an etch stop layer 137, a structured layer 310 disposed on the etch stop layer 137 and including a plurality of processed structures 329, the processed structures 329 being inclined relative to the etch stop layer 137, a planarizing backfill layer 315 disposed on the plurality of processed structures 329, the planarizing backfill layer 315 defining a substantially unstructured major surface 321 of the planarizing backfill layer 315 having a surface roughness Ra, and an adhesive layer 140 disposed on the substantially unstructured major surface 321 of the planarizing backfill layer 315, the adhesive layer 140 bonding the structured film 351 to the major surface 191 of the waveguide 190, the adhesive layer 140 having an average thickness ta. In some embodiments, the difference in refractive index between the planarizing backfill layer 315 and the structured layer 310 is at least 0.25 for at least a first wavelength W1 in the range of 400 nm to 2500 nm, or other ranges described elsewhere herein. <ta<(1 / 4)W1である。

[0034] In some embodiments, the structured layer 110, 210, or 310 includes multiple sublayers. For example, the structured layer can be formed by etching an unstructured layer, as further described elsewhere herein, where the unstructured layer can include a stack of sublayers, such that the resulting engineered structure has sublayers. Figure 6B is a schematic cross-sectional view of an article 301' including a structured film 351' bonded to a waveguide 190, according to some embodiments. The structured film 351' includes structured layers 310a, 310b including a first sublayer 310a disposed on a second sublayer 310b.

[0035] In some embodiments, the plurality of processed structures 129, 229, or 329 includes structures having at least two different heights. For example, structures having at least two different heights can be formed by etching through an etch resist layer having structures having at least two different heights. For example, with reference to FIGS. 7A-7C, mask layer 131 can be omitted, etch resist layer 125, 225, or 325 can be a multi-level resist layer, and a pattern transfer process can provide a multi-level pattern in previously unstructured layer 110′, 210′, or 310′, respectively. FIG. 6C is a schematic cross-sectional view of an article 301″ including a structured film 351″ bonded to a waveguide 190, according to some embodiments. Structured film 351″ includes a structured layer 310″ including structures 329a and 329b having different heights. In some embodiments, structured layer 310″ includes multiple sublayers, with taller structures 329a including more sublayers than shorter sublayers 329b. For example, the top sublayer of structure 329b but not structure 329a may be etched away.

[0036] 7A-7C show schematic processes for making structured films 150, 250, and 350, respectively. An input film (e.g., a roll of film) includes a polymer substrate 130, an etch stop layer 137 disposed on the polymer substrate 130, an unstructured layer 110' (210', 310', respectively) disposed on the unstructured layer, and a mask layer 131 disposed on the unstructured layer. In step A (A', A'' respectively), an etch resist layer 125 (225, 325, respectively) is disposed on the mask layer 131. The etch resist layer may be formed via replication from a tool as further described elsewhere herein. Mask layer 131 may be optionally omitted (e.g., if relatively low aspect ratio structures are desired or if a multi-level structured layer is desired), in which case the etch resist layer may function as an etch mask for etching into the unstructured layer. In step B (B', B'' respectively), a breakthrough etch is performed, followed by etching of the mask layer 131. Both etching steps can utilize, for example, reactive ion etching (RIE). In step C (C', C'' respectively), etching continues until the etch resist layer 125 (225, 325 respectively) is removed. In step D (D', D'' respectively), the etching conditions are changed (e.g., to oxygen RIE) to etch the unstructured layer 110' (210', 310' respectively) until the via reaches the etch stop layer 137. In step D' of FIG. 7C, a directional etch (e.g., directional RIE) is performed at an oblique angle to form a sloped structure. Etching at an oblique angle to form a sloped structure is described, for example, in U.S. Pat. No. 10,670,862 (Vallius et al.) and U.S. Patent Application Publication No. 2016 / 0033784 (Levola et al.). In step E (E′, E″, respectively), etching continues until mask layer 131 is removed. Structured layer 110 (210, 310, respectively) can combine with exposed portions of the mask layer to define a major surface 111 (211, 311, respectively) that faces away from polymer substrate 130.In step F (F', F'', respectively), the vias are backfilled (e.g., by atomic layer deposition) with a planarizing backfill. The planarizing backfill can have a major surface 116 (216, 316, respectively) that faces and substantially conforms to (e.g., deviates from conformance by no more than 20% or no more than 10% by t2) major surface 111 (211, 311, respectively). The planarizing backfill has a desired roughness Ra, with troughs or valleys that correspond to the underlying vias. 0 In some embodiments, the surface roughness can be determined by a roughness ratio of Ra <Ra 0 Step G (G', G'' respectively) is performed to reduce Ra to less than about 30 nm, or less than about 20 nm, or less than about 10 nm, or less than about 5 nm, or less than about 2 nm, or less than about 1 nm, or less than about 0.5 nm. In some such embodiments, or in other embodiments, Ra 0 -Ra is greater than 10 nm, or greater than 20 nm, or greater than 40 nm, or greater than 80 nm. In some embodiments, smoothing the rough surface is performed by chemical mechanical planarization (e.g., using an abrasive with a corrosive chemical slurry), as generally described, for example, in U.S. Pat. No. 6,623,355 (McClain et al.) and U.S. Pat. No. 9,200,180 (Banerjee et al.). In some embodiments, smoothing the rough surface is performed by a combination of mechanical polishing and dry etching, as generally described, for example, in U.S. Pat. No. 6,858,537 (Brewer). In step H (H, H', respectively), an adhesive layer 140 is applied to the planarized backfill layer 115 (215, 315, respectively). In some applications (e.g., visible optical applications), a surface roughness of less than 5 nm, or less than 2 nm, or less than 1 nm, or less than 0.5 nm may be preferred. In some embodiments, a removable liner is applied to adhesive layer 140 before the structured film is covered with a sheet and / or stored.

[0037] The etching process of Figures 7A-7C may be a plasma etching process. When high aspect ratio structures are desired, ion-assisted plasma processing is advantageously used. Methods for achieving anisotropic etching include reactive ion etching (RIE), high density ion source processing, or a combination of high density ion source processing and RIE. High density plasma can be generated by inductive radio frequency or microwave coupling, or by a helicon ion source. Linear high density plasma sources are particularly advantageous for forming high aspect ratio features. Combining high density plasma with RIE allows decoupling ion generation (by high density plasma) from ion energy (by RIE bias voltage).

[0038] The RIE process involves etching portions of the major surface that are not protected by a masking layer to form structures (e.g., nanostructures) on the substrate. In some embodiments, the method can be performed using a continuous roll-to-roll process referred to as "cylindrical reactive ion etching" (cylindrical RIE). Cylindrical RIE utilizes a rotating cylindrical electrode to provide anisotropically etched nanostructures on the surface of the article's substrate. In general, cylindrical RIE can be described as follows: A rotatable cylindrical electrode ("drum electrode"), powered by radio frequency coupling, and a grounded counter electrode are provided inside a vacuum vessel. The counter electrode can include the vacuum vessel itself. An etchant gas is fed into the vacuum vessel, and a plasma is ignited and maintained between the drum electrode and the grounded counter electrode.

[0039] The continuous substrate containing the patterned masking layer can then be wrapped around the drum, and the substrate can be etched in a direction normal to the plane of the substrate. The exposure time of the substrate can be controlled to obtain a predetermined etch depth in the resulting nanostructures. The process can be carried out at an operating pressure of about 1-10 millitorr. Cylindrical RIE is described, for example, in U.S. Patent No. 8,460,568 (David et al.).

[0040] When multiple materials are present, the chemistry of the plasma environment can be controlled to achieve etch selectivity. Oxygen and mixtures of oxygen with fluorinated gases are used to etch carbon-containing materials such as polymers, diamond-like carbon, and diamond. The concentration of fluorine in the plasma can be selected to optimize the etch rate and selectivity. Typically, small amounts of fluorinated gas are used to dramatically increase the etch rate of hydrocarbon polymers by as much as 300%.

[0041] Siliceous materials (silicon dioxide, SiO x For example, mixtures of fluorocarbons such as CF4, C2F6, and / or C3F8 are used in combination with oxygen to etch siliceous materials (e.g., diamond-like glass, silicon nitride, silicon carbide, silicon oxycarbide, polysiloxanes, silsesquioxane (SSQ) resins, etc.). The etch selectivity of siliceous materials to hydrocarbon polymers can be closely tuned by obtaining the etch profile of these materials as a function of the F / O atomic ratio in the plasma feed gas mixture. Oxygen-rich conditions provide excellent selectivity for etching hydrocarbon polymers and diamond-like carbon (DLC) while using siliceous materials as a masking layer. In contrast, fluorine-rich conditions provide excellent selectivity for etching siliceous materials while using hydrocarbon polymer-based masking materials.

[0042] Fluorinated plasma chemistries can be used to etch other masking materials, such as tungsten, whose fluorides are volatile. Chlorine-containing gas mixtures can be used to etch materials, such as aluminum and titanium, whose chlorides are volatile. Oxides, nitrides, and carbides of these etchable metals can also be etched using chlorine-based chemistries. Silicon nitride, aluminum nitride, and titanium oxide are high refractive index materials that can be etched with chlorine chemistries.

[0043] Various layers (e.g., mask layer 131, etch stop layer 137, layers 110', 210', 310', backfill layer 115, 215, 315, or adhesive layer 140) can be deposited using various deposition methods, taking into account the type of material and layer thickness. Suitable deposition methods can include, for example, chemical vapor deposition (CVD), sputter coating, physical vapor deposition (PVD), atomic layer deposition (ALD), or combinations thereof. Thin layers or films can be coated on flat or structured surfaces using coating methods known in the art, such as slot-die coating, slide coating, curtain coating, knife coating, blade coating, dip coating, and spin coating. Slot-die coating equipment is described, for example, in U.S. Pat. Nos. 5,639,305 (Brown et al.) and 7,591,903 (Maier et al.). Spin coaters are described, for example, in U.S. Pat. No. 6,033,728 (Kikuchi et al.).

[0044] The planarizing backfill layer (e.g., 115, 215, 315) can be formed from any suitable material. Preferably, the planarizing backfill layer is formed from a material having a refractive index at least 0.2, or at least 0.25, or at least 0.3, or at least 0.35 higher than the refractive index of the structured layer (e.g., 115, 215, 315), at least for the first wavelength W1. Suitable materials for the backfill layer include zirconia or titania-filled acrylate resins, which may be deposited, for example, by coating; metal oxides, nitrides, and oxynitrides, including, for example, oxides, nitrides, and oxynitrides of, for example, Si, Ti, Zr, Hf, Nb, Ta, or Ce, which may be deposited, for example; and parylene, which may be applied, for example, by coating. Since silicon is a semimetal, silicon oxides, silicon nitrides, and silicon oxynitrides are considered to be metal oxides, metal nitrides, and metal oxynitrides, respectively. In some cases, for optical applications involving visible light, titania (TiO2) may be preferred, while for applications involving near infrared light, silicon or other metal oxides may be used. The structured layer can be formed, for example, from any of the low refractive index materials described elsewhere herein. The structured layer can be, for example, a fluoropolymer layer. In some embodiments, the structured layer comprises a fluoropolymer and the planarizing backfill layer comprises a metal oxide, nitride, or oxynitride. In some embodiments, the structured layer has a refractive index of 1.4 or less, and the planarizing backfill layer has a refractive index of at least 1.65 or at least 1.7, at least for the first wavelength W1.

[0045] In some embodiments, the wavelengths of interest are in the visible or near infrared range. Thus, the first wavelength W1 may be in the range of 400 nm to 2500 nm. In some embodiments, visible wavelengths are of primary interest. Thus, the first wavelength W1 may be in the range of 400 nm to 700 nm. In some embodiments, near infrared wavelengths are of primary interest. Thus, the first wavelength W1 may be in the range of 700 nm to 2500 nm, or 800 nm to 2000 nm, for example. Some specific near infrared wavelengths that may be of interest depending on the application include, for example, 850 nm, 905 nm, 940 nm, 1060 nm, 1330 nm, and 1550 nm.

[0046] In some embodiments, the etch-resistant layer 125, 225, or 325 comprises a silicone-containing polymer. In some embodiments, the etch-resistant layer comprises a siloxane, a silicone, or a silsesquioxane. In some embodiments, the etch-resistant layer comprises a crosslinked acrylate. Suitable etch-resistant layers are described, for example, in U.S. Pat. No. 5,811,183 (Shaw et al.). The etch-resistant layer may have a total thickness in the range of, for example, 50 nm to 500 nm.

[0047] The etch resist layer 125, 225, or 325 can be formed using different pattern printing, transfer, tiling, copying, or replication techniques, which can include, for example, photolithography, e-beam lithography, grayscale lithography, two-photon lithography, or nanoimprint lithography, or a master mold fabricated by microcontact printing (μCP). Replication techniques (e.g., nanoreplication) can include, for example, casting and curing a resin against a structured surface of a tool. Suitable casting and curing methods, as well as suitable resins for use in such methods, are described, for example, in U.S. Pat. Nos. 5,175,030 (Lu et al.) and 5,183,597 (Lu), and U.S. Patent Application Publication No. 2012 / 0064296 (Walker, JR. et al.). Other useful methods and / or materials for forming etch resist layers are described, for example, in U.S. Patent Nos. 8,658,248 (Anderson et al.), 5,811,183 (Shaw et al.), and 6,045,864 (Lyons et al.).The structured tool may be fabricated using any suitable fabrication method, such as by photolithography or electron beam lithography to prepare a tooling master, a metal copy thereof, a polymer copy of either the tooling master or the metal copy thereof, a polymer copy of such a polymer copy, a directly written tool or any copy thereof, a copy of a structured liner or any copy thereof. Suitable fabrication methods are described, for example, in International Publication No. WO 2009 / 002637 (Zhang et al.), and US Patent Application Publication No. 2007 / 0065636 (Merrill et al.), and US Patent Application Publication No. 2014 / 0193612 (Yu et al.), and US Patent No. 8,460,568 (David et al.). The tool may be made, for example, by diamond turning. Exemplary diamond turning systems and methods are described, for example, in US Patent No. 7,350,442 (Ehnes et al.), US Patent No. 7,328,638 (Gardiner et al.), and US Patent No. 6,322,236 (Campbell et al.).An example of patterning subwavelength gratings can be found in Chun-Wei Liu, Jiwang Yan, Shih-Chieh Lin, “Diamond turning of high-precision roll-to-roll imprinting molds for fabricating subwavelength gratings,” Opt. Eng. 55(6), 064105(2016), doi:10.1117 / 1.OE.55.6.064105.).

[0048] Mask layer 131 can be made of any material that has suitable etch selectivity with respect to layers 110', 210', or 310'. In some embodiments, mask layer 131 is or includes a metal or silicon-containing metal oxide. Examples include chromium (Cr), aluminum (Al), copper (Cu), titanium (Ti), tungsten (W), germanium (Ge), iridium (Ir), platinum (Pt), ruthenium (Ru), osmium (Os), rhenium (Re), alloys thereof, or silicon-containing oxides thereof. In some embodiments, mask layer 131 is made of SiO2, Si x O y N z (x=1, y=1~2, z=0~1), or Si x Al y O z (x=1, y=0-1, z=1-2). Useful oxides are described, for example, in U.S. Patent Application Publication No. 2015 / 0214405 (Nachtigal et al.). Useful materials include, for example, titanium nitride (TiN), aluminum oxide (Al2O3), aluminum and chromium (Al / Cr) metal alloys, Si x C y H z (x=1, y=1~4, z=1~4), or Si x C y N z H n (x=1, y=1~4, z=0~1, n=1~4), Si x N y (x=1, y=0~1), SiOx (x=1-2), SiH x (x=1-4). Other suitable materials include diamond-like glasses, for example, as described in U.S. Patent No. 8,034,452 (Padiyath et al.). Mask layer 131 may also be referred to as a hard mask layer.

[0049] The etch stop layer 137 can be made of any material that has suitable etch selectivity with respect to layers 110', 210', or 310'. In some embodiments, the etch stop layer 137 is made of a metal (e.g., Cr, Al, Ti, Zr, Ta, Hf, Nb, Ce, or alloys thereof), a metal oxide (e.g., Al2O3 or Si x Al y O z (e.g., x=1, y=0-1, z=1-2), or an oxide of any of these metals; or Si x O y N z (e.g., x=1, y=1-2, z=0-1)), or metal nitrides (e.g., nitrides of any of these metals, or Si x O y In some embodiments, the etch stop layer 137 is or includes, for example, indium tin oxide, tin oxide, or alumina (Al2O3). Useful materials include, for example, Si x C y H z (For example, x=1, y=1-4, z=1-4), Si x C y N z H n (For example, x=1, y=1-4, z=0-1, n=1-4), Si x N y (e.g., x=1, y=0-1), SiO x (e.g., x=1~2), Si x O y N z (e.g., x=1, y=1-2, z=0-1), or SiH x(e.g., x=1-4). Other suitable materials include, for example, diamond-like glass. In some embodiments, the etch stop layer 137 is optically transparent, which may be understood to mean that the etch stop layer has an average optical transmittance for substantially normally incident light of at least 60% for a wavelength range of 400 nm to 700 nm.

[0050] The average thickness of mask layer 131 and / or etch stop layer 137 may be, for example, in the range of about 1 nm to about 200 nm, or about 2 nm to about 50 nm, or about 2.5 nm to about 10 nm. Mask layer 131 can have, for example, an average thickness less than 50 nm, or less than 25 nm, and / or greater than 5 nm. Etch stop layer 137 can have, for example, an average thickness less than 25 nm and / or greater than 2 nm.

[0051] The etch stop layer 137 can be selected from materials having a desired optical transmittance at the wavelength of interest for a suitable thickness. In some embodiments, the etch stop layer 137 has an optical transmittance for substantially normally incident light of at least 60%, or at least 70%, for at least the first wavelength W1. In some embodiments, the structured layer is formed from one or more unstructured layers (e.g., any of the layers 110', 210', 310' may be a single layer or may include multiple sublayers). In some embodiments, the one or more unstructured layers have an optical transmittance for substantially normally incident light of at least 60%, or at least 70%, for at least the first wavelength W1.

[0052] 8 is a schematic cross-sectional view showing one or more unstructured layers 777, incident light 773, and transmitted light 774. Incident light 773 is incident substantially perpendicularly (e.g., within 20 degrees, or within 10 degrees, or within 5 degrees of perpendicular) on one or more unstructured layers 777, which may be a single layer (e.g., an unstructured layer corresponding to any one of layers 131, 137, 110', 210', 310', or formed from any material of layers 115, 215, or 315 and having a thickness of t1+t2) or may be a stack of layers (e.g., corresponding to layers 131, 137 and 110', 210', or 310'). Incident light 773 is represented generally as having a wavelength λ in the range λ1 to λ2. The range λ1-λ2 may be, for example, 400 nm-2500 nm, or 400 nm-700 nm, or 700 nm-2500 nm. The wavelength λ may be a single wavelength (e.g., a first wavelength W1), or a range of wavelengths (e.g., 400 nm-700 nm). In some embodiments, the one or more unstructured layers 777 may have an optical transmittance for substantially normally incident light of at least 60%, or at least 70%, or at least 80%, for at least the first wavelength W1. In some embodiments, the one or more unstructured layers 777 may have an average optical transmittance for substantially normally incident light (unweighted average of optical transmittance over a given wavelength range) of at least 50%, or at least 60%, or at least 70%, or at least 80%, for example, for the wavelength range of 400 nm-2500 nm or 400 nm-700 nm.

[0053] In some embodiments, a wafer master (e.g., a semiconductor wafer substrate, with a nanopattern etched into the wafer surface, typically silicon or silicon dioxide on silicon) is used in making structured films that can be used, for example, to apply nanostructures to a waveguide. The wafer master can be generated using standard mastering techniques, such as, for example, e-beam lithography or immersion lithography. The master pattern can then be copied into a series of process intermediates, which can include polymer copies (imprint resist on wafer), polymer stamps (imprint resist on polymer), tiled polymer mothers (tiled wafer patterns on large glass substrates), electroformed nickel shims, and welded nickel sleeves. The welded nickel sleeves can be used, for example, in a sequential casting and curing (e.g., nanoreplication) process to produce structured films. The wafer patterns can be used in single element layouts or can be composited with other patterns from other wafers to form composite layouts. Each may be carried through the process as a single element and then combined during the lamination step, or, for example, all but one may be combined in a tiled polymer mother process and made into a single composite film roll, and the remaining element may be laminated, for example, onto the opposite side of the waveguide and not combined with the other elements.

[0054] In some embodiments, a synthesis approach is utilized in which individual nanopatterns are synthesized in an intermediate such as a tiled polymer mother, which is used to fabricate the synthetic shims, sleeves, and films. A liner on the structured film may be laser kiss-cut to expose the adhesive in the structured regions of the film (e.g., optical coupler regions), and the entire film can be laminated to a waveguide. This route is useful, for example, when all the couplers are on the same side of the waveguide. In some embodiments, a single-element approach is utilized in which the individual nanopatterns are transferred from the wafer to the film as a single element. In this case, the number of films can be the same as the number of wafers. The elements from each film can be prepared as described elsewhere herein and synthesized during lamination. In some embodiments, a combination of synthesis and single-element approaches is used, where some, but not all, of the individual nanopatterns are applied to one side of the waveguide, and the remaining individual nanopatterns are applied to the opposite side of the waveguide in the single-element approach.

[0055] The laminated waveguide may be, for example, laser cut around the bonded coupler regions to remove weeds. In some embodiments, the resulting laminate represents the finished optical article. In other embodiments, the laminate is processed in a further separate step to produce the final optical article. In some embodiments, the waveguide may be singulated, for example, into multiple near-to-eye (NTE) augmented reality (AR) waveguides.

[0056] Working Example Structured film articles were prepared by using nanoreplication, solvent coating, plasma etching, vacuum thin film deposition, and lamination techniques. The resulting structures are optical articles having a nanostructured optically functional layer (titanium dioxide) bonded to a receptor substrate such as a polished glass sheet.

[0057] These examples are for illustrative purposes only and are not intended to be limiting. All parts, percentages, ratios, etc. in the examples and elsewhere herein are by weight unless otherwise indicated. Solvents and other reagents used were obtained from Sigma-Aldrich Chemical Company (St. Louis, Missouri) unless otherwise indicated. [Table 1]

[0058] Preparation Example Preparation example 1 (PE1) First, an acrylate solution was prepared by adding 75 wt% PHOTOMER 6210 to 25 wt% SR238 and 0.5% TPO to form a first acrylate mixture. 93 wt% of the first acrylate mixture was manually mixed with 7 wt% HFPO-UA to obtain a second acrylate mixture. Then, 14 wt% of the second acrylate mixture was manually combined with 43 wt% PGME and 43 wt% MEK to form an acrylate solution.

[0059] Preparation example 2 (PE2) An adhesion promoter solution was prepared by adding 0.3 wt % of Compound 01 to 99.7 wt % MEK and 0.003 wt % TPO-L.

[0060] Preparation example 3 (resin D) An acrylate resin mixture prepared by mixing a combination of PHOTOMER 6210, SR238, SR351, and TPO in a weight ratio of 60 / 20 / 20 / 0.5.

[0061] Preparation example 4 (base material 01) Substrates with a release layer are prepared by coating a peelable layer onto the ST505 film on a roll-to-roll vacuum coater similar to the coater described in U.S. Patent Application Publication No. 20100316852 (Condo et al.) with the addition of a second evaporator and curing system positioned between the plasma pretreatment station and the first sputtering system, and using an evaporator as described in U.S. Patent No. 8,658,248 (Anderson and Ramos).

[0062] ST505 films are prepared for coating by treating them with nitrogen plasma to improve adhesion of the metal layer. The films were treated with nitrogen plasma operating at 120 W with a titanium cathode using a web speed of 9.8 meters / min while the backside of the film was kept in contact with a coating drum cooled to 0 °C.

[0063] A release layer of 90% / 10% Si / Al is deposited on the prepared ST505 substrate in-line with the previous plasma treatment step. A conventional AC sputtering process employing Ar gas and operating at 16 kW power is used to deposit a 7 nm thick layer of SiAl alloy on the substrate. The SiAl-coated PET substrate is then unwound.

[0064] An acrylate transfer layer SR833 with less than 1 wt% of Compound 1 is applied to the release layer by ultrasonic spraying and flash evaporation. The liquid monomer flow to the evaporator is 0.67 mL / min. The nitrogen gas flow rate is 100 standard cubic centimeters per minute (SCCM) and the evaporator temperature is set at 500°F (260°C). The process drum temperature is 14°F (-10°C). This monomer coating is then cured directly downstream with an electron beam curing gun operating at 7.0 kV and 10.0 mA to obtain a 180 nm thick acrylate layer.

[0065] Preparation example 5 (FPI) Pentafluorobenzoylmethoxyphenylphosphine oxide is synthesized under vacuum and yellow ambient light in a flame-dried, three-necked round-bottom flask equipped with a thermocouple, magnetic stir bar, and liquid addition funnel. The round-bottom flask is flushed with dry nitrogen and charged with 9.92 g (58.3 mmol) of dimethoxyphenylphosphine.

[0066] The liquid addition funnel is charged with 13.44 g (58.3 mmol) of pentafluorobenzoyl chloride and the reactor is connected to vacuum. The round-bottom flask is cooled in a dry ice / isopropanol bath and the pentafluorobenzoyl chloride is added dropwise at a rate sufficient to keep the reaction temperature below 15° C. During this time the reaction mixture becomes a light yellow-orange oil of pourable viscosity. The pentafluorobenzoyl methoxyphenylphosphine oxide is recovered in quantitative yield and stored in a brown glass jar.

[0067] Preparation example 6 (HFPO-FCA) In a 500 mL round bottom flask equipped with a stir bar and septum, under nitrogen gas, 120 g (0.0663 mol, 1810 MW) of HFPO oligomer diacrylate (Mn=2000 g / mol, prepared according to the synthetic method generally described in U.S. Pat. No. 9,718,961 (Corveleyn et al.)) and 120 g of 1,1,1-trifluorotoluene, previously dried as a 50% solid solution over 4 Angstrom molecular sieves in a septum capped bottle, are added. Next, 1.42 g (1.46 mL, 0.007366 mol, 193.32 number average molecular weight) of N-methyl-3-aminopropyltrimethoxysilane is added and the reaction is stirred at room temperature (RT) for 2 hours, at which point an aliquot is evaluated by 1H Fourier transform nuclear magnetic resonance spectroscopy (FT-NMR) in D8-tetrahydrofuran / Freon 113. The reaction is then concentrated on a rotary evaporator at 2 torr and 57° C. for approximately 30 minutes and bottled under nitrogen.

[0068] Hypothetical Example 1 The optical article is prepared using the following process.

[0069] Step 1. Nanoreplication of template layer A nanostructured tooling film is prepared by die coating resin D onto a polycarbonate film. The coated film is pressed onto a nanostructured nickel surface attached to a steel roller controlled at 60 °C using a rubber covered roller at a speed of 15.2 meters per minute. The nanostructured nickel surface consists of twelve 6 mm x 6 mm patterned regions with features ranging in size from 75 nm to 500 nm. The patterned regions consist of a multi-pitch pattern with pitches of 150 nm, 200 nm, and 250 nm, with feature widths half the pitch (75 nm, 100 nm, 125 nm).

[0070] The features are arranged in a square grid with pitch varying in both axes, resulting in a repeating cell of 9 units with rectangles of all combinations of widths as mentioned above. In this repeating cell, the 150 nm pitch section has 27 features, the 200 nm pitch section has 20 features, and the 250 nm pitch section has 16 features. The features are approximately 200 nm tall and have sidewall angles of approximately 4 degrees.

[0071] The coating thickness of resin D on the film is sufficient to completely wet the nickel surface and form a rolling bead of resin when the coated film is pressed onto the nanostructured nickel surface. The film, while in contact with the nanostructured nickel surface, is exposed to radiation from two Fusion UV lamp systems (obtained under the trade name "F600" from Fusion UV Systems, Gaithersburg, MD), both fitted with D bulbs operating at 142 W / cm. After peeling the film from the nanostructured nickel surface, the nanostructured side of the film is again exposed to radiation from the Fusion UV lamp systems.

[0072] Step 2: Peeling A silicon-containing release film layer, fabricated by methods described in U.S. Pat. Nos. 6,696,157 (David et al.) and 8,664,323 (Iyer et al.) and U.S. Patent Application Publication No. 2013 / 0229378 (Iyer et al.), is applied to the nanostructured tooling film in a parallel plate capacitively coupled plasma reactor. The chamber has a 1.7 m 2 (18.3ft 2 The electrode has a central cylindrical powered electrode with a surface area of ​​100 nm.

[0073] The nanostructured tooling film is placed on top of the powered electrode and the reactor chamber is pumped down to a base pressure of less than 2 millitorr. O2 gas is introduced into the chamber at a flow rate of 1000 SCCM. Processing is carried out using a plasma-enhanced CVD method by coupling radio frequency (RF) power into the reactor at a frequency of 13.56 MHz and an applied power of 2000 Watts. Processing time is controlled by moving the nanostructured tooling film through the reaction zone at a speed of 30 feet / min, resulting in an exposure time of approximately 10 seconds. After deposition is completed, the RF power is turned off and gases are evacuated from the reactor.

[0074] Following the first treatment, a second plasma treatment is performed in the same reactor without returning the chamber to atmospheric pressure. HMDSO gas is flowed into the chamber at approximately 1750 SCCM to achieve a pressure of 9 millitorr. 13.56 MHz RF power is then coupled into the reactor with an applied power of 1000 W. The film is then transported through the reaction zone at a speed of 9.1 meters / minute (30 feet / minute), resulting in an exposure time of approximately 10 seconds. At the end of this treatment time, the RF power and gas supply are stopped, the chamber is returned to atmospheric pressure, and the release-treated nanostructured tooling film is removed from the chamber.

[0075] Step 3: Pattern transfer film A pattern transfer film is prepared by depositing an etch stop layer and a pattern transfer layer on an 11.5 inch wide ST505 PET substrate film by reactive sputtering and organic vapor deposition in a system similar to those described in U.S. Patents 5,440,446 (Shaw et al.) and 7,018,713 (Padiyath et al.). The substrate film is coated in a roll-to-toll (R2R) format. In the first pass through the system, the substrate film is treated with nitrogen plasma from an unbalanced dc magnetron cathode with a titanium target at a power of 50 W and a nitrogen flow rate of 100 SCCM.

[0076] Immediately after the film was plasma treated, approximately 12 nm of SiAlO x A base etch stop layer of 10 ...

[0077] SiAlO was then deposited using the organic deposition system and method described in U.S. Pat. No. 8,658,248 (Anderson et al.). xThe surface is vapor-coated with a layer of 90% HFPO-FCA / 9% HFPO / 1% FPI (wt%) to a thickness of approximately 100 nm. A line speed of 3.81 meters / minute (12.5 feet / minute) is maintained with the backside of the film in contact with a coating drum cooled to 0°C. Prior to coating, the monomer is degassed under vacuum to a pressure of 20 millitorr. The liquid is pumped to an ultrasonic atomizer using a syringe pump at a liquid flow rate of 1.0 mL / min and a flow rate of 10 SCCM of nitrogen gas is delivered to the atomizer. The liquid is flash evaporated at 250°C to produce SiAlO x The vapor stream is condensed on the film surface and cured by UV irradiation using a low pressure mercury arc lamp.

[0078] Using the same method as described for the base etch stop layer, a SiAlO layer approximately 12 nm thick was deposited on the HFPO-FCA / HFPO / FPI surface. x A top etch stop layer of 1000 .ANG. is deposited.

[0079] Step 4: Adhesion promoter The adhesion promoter solution of PE2 was coated onto the pattern transfer film made in step 3 using slot die coating. A Harvard syringe pump at 3 SCCM is used to pump the solution through the slot die onto the film moving at a speed of 6 meters / min. The film is then transferred to a 65° C. oven for 1.5 minutes, after which it is cured using a Fusion H bulb, followed by winding.

[0080] Step 5: Resist transfer The release treated nanostructured tooling film from step 2 is slot die coated with acrylate solution PE1 at 3 meters / min. The solution is coated at a width of 10.16 cm and pumped at a rate of 1.05 SCCM using a Harvard syringe pump. The coating is partially cured 1.5 meters from the solution application using a 405 nm UV-LED system powered at 40 volts and 0.2 amps. The coating has a UV-visible spectrum of approximately 0.005 W / cm.2 is subjected to irradiance of

[0081] The film is then allowed to dry at ambient conditions for 3 minutes before being placed in a nip where the pattern transferred film from step 4 (along with the base etch stop, transfer layer, top etch stop, and adhesion promoter) is laminated to the PE 1 coated release treated template film.

[0082] The nip consists of a 90 durometer rubber roll and a steel roll set at 37° C. The nip is engaged by two Bimba air cylinders pressed at 0.28 MPa.

[0083] Cure the coated PE1 acrylate solution using a Fusion H bulb and separate the first acrylate mixture from the release treated template film leaving a cured PE1 coating on the transfer film for the entire 6 mm x 6 mm patterned area. Set the web tension to approximately 0.0057 N / m.

[0084] Step 6: Etching the transfer layer The patterned transfer film from step 5 is etched according to methods for reactive ion etching to produce an etched pattern transfer film.

[0085] Reactive ion etching is performed on the patterned film in the same reactor chamber used to deposit the release treatment layer in step 2. After the patterned transfer film is placed on the powered electrode, the reactor chamber is pumped down to a base pressure of less than 1.3 Pa (1 millitorr). A mixture of PF-5060 and oxygen gas is flowed into the chamber at flow rates of 100 SCCM and 50 SCCM, respectively. Subsequently, 13.56 MHz RF power is coupled into the reactor with an applied power of 7500 W. The film is then transported through the reaction zone at a speed of 1.2 meters / minute (4 feet / minute) to achieve an exposure time of about 75 seconds in order to transfer the pattern to the top etch stop layer.

[0086] Once the first etch step is complete, the RF power is turned off and the gases are evacuated from the reactor. Following the first etch, a second reactive ion etch process is performed in the same reactor without returning the chamber to atmospheric pressure. Oxygen is flowed into the chamber at a flow rate of 275 SCCM. 13.56 MHz RF power is then coupled into the reactor with an applied power of 7500 W.

[0087] The patterned transfer film is then transported through the reaction zone at a speed of 7.6 meters / minute (25 feet / minute), resulting in an exposure time of approximately 12 seconds. At the end of this treatment period, the RF power and gas supplies are turned off and the chamber is returned to atmospheric pressure.

[0088] Additional information regarding materials and processes for sequential reactive ion etching through a nanostructured mask, as well as further details of the reactor environment, can be found in US Pat. No. 8,460,568 (David et al.).

[0089] Step 7: TiO2 backfill A backfilled nanostructured film is formed by depositing TiO2 on the etched pattern transfer film from step 6. The TiO2 backfill layer is formed from titanium tetra(isopropoxide) (TTIP) precursor using a spatial atomic layer deposition (ALD) process. Planar coating is performed in a spatial R2R ALD machine as described in WO 2017 / 172531 (Lyons et al.). TiO2 is deposited using TTIP heated to 80°C with 300 SCCM N2 push gas and a plasma discharge (approximately 0.50 mA / cm2) in an environment of 1.1 Torr N2 and 0.3 Torr CO2. The ALD chamber is heated to 100°C.

[0090] The film is moved through the ALD chamber for multiple passes at 30.48 meters / min (100 feet / min), with one precursor exposure and one plasma exposure per ALD cycle, and 72 ALD cycles per chamber pass. The film is moved through the ALD chamber for 10-50 passes to obtain a TiO2 layer thick enough to fill the etched nanostructures in the transferred film and form a flat surface over the top of the nanostructured regions of the transferred film.

[0091] Step 8: Solution Coating of Adhesive Layer An adhesive layer is formed on the surface of the TiO2 backfill nanostructured film from step 7 by slot die coating the adhesive coating solution in a roll-to-roll process. An adhesive coating solution is made by diluting a quantity of FG1901 G with enough cyclohexane to produce a solution containing 0.33 wt% total solids. This solution is coated onto the film from step 5 at a speed and flow rate that produces a wet coating thickness of about 9 micrometers. The coated web travels about 2.4 m (8 ft) before entering a 9.1 m (30 ft) conventional air flotation dryer with all three zones set at 80° C. (176° F.). After drying, the adhesive coating is about 30 nanometers thick.

[0092] Step 9: Lamination onto glass substrate The optical article is formed by laminating the adhesive coated nanostructured film from step 8 to a glass substrate. A suitable glass substrate is a 1.1 mm thick, 76.2 mm diameter Eagle XG glass wafer with a surface roughness of less than 1 nm RMS. The adhesive side of the structured film is placed on one surface of the glass wafer and the film is laminated to the glass substrate by passing it through a HL-100 Hot Roll Laminator (ChemInstruments, West Chester Township, Ohio) set at 80 psi, 40 cm / min, and 115°C.

[0093] Hypothetical Example 2 Steps 1-7 are completed as in Hypothetical Example 1.

[0094] Step 7a: Thinning of TiO2 backfill The TiO2 backfill nanostructured film constructed in step 7 is reactive ion etched to reduce the thickness of the planarized ALD TiO2 layer. The film is reactive ion etched in the same reactor chamber used to deposit the release treatment layer in step 2 of hypothetical example 1. After the patterned transfer film is placed on the powered electrode, the reactor chamber is pumped down to a base pressure of less than 1.3 Pa (1 mTorr). Nitrogen trifluoride is introduced into the chamber at a flow rate of 1000 SCCM. Subsequently, 13.56 MHz RF power is coupled into the reactor with an applied power of 7500 W. The film is then transported through the reaction zone to achieve a planar removal rate of 100 nm per minute of exposure time. The exposure time is selected to leave a thin planar layer of TiO2 on the nanostructured film such that the residual layer is less than 50 nm thick.

[0095] Steps 8 and 9 are repeated as in Hypothetical Example 1.

[0096] Hypothetical Example 3 An optical article is prepared as described in Hypothetical Example 1 or Hypothetical Example 2, except that in step 1, a nanostructured tooling film is prepared on Substrate 01 instead of polycarbonate.

[0097] After step 9, the 90% / 10% Si / Al layer of Substrate 01 is weakened by exposing it to UV light through the ST505 film. After UV exposure, the ST505 substrate is removed by peeling it off the structure, thereby leaving the structure attached to the glass wafer.

[0098] Terms such as "about" will be understood by those of skill in the art in the context in which they are used and described herein. Unless otherwise clear to those of skill in the art in the context in which they are used and described herein, the use of "about" as applied to quantities describing feature sizes, quantities, and physical properties will be understood to mean within 10 percent of a particular value. A quantity given as about, approximately a particular value may be exactly that particular value. For example, unless otherwise clear to those of skill in the art in the context in which they are used and described herein, an amount having a value of about 1 means that the amount has a value between 0.9 and 1.1, and may even be 1.

[0099] All references, patents, or patent applications referenced above are hereby incorporated by reference in their entirety. In the event of any inconsistency or contradiction between any of the incorporated references and this application, the information in the foregoing description shall prevail.

[0100] Descriptions of elements in the drawings should be understood to apply equally to corresponding elements in other drawings unless otherwise indicated. Although specific embodiments have been illustrated and described herein, those skilled in the art will appreciate that the specific embodiments illustrated and described may be replaced by various alternative and / or equivalent embodiments without departing from the scope of the present disclosure. The present application is intended to cover any adaptations, or variations, or combinations of the specific embodiments discussed herein. Accordingly, the present disclosure is intended to be limited only by the claims and the equivalents thereof.

Claims

1. A waveguide; 1. A structured film comprising: A polymer substrate; an etch stop layer disposed on the polymer substrate; a structured layer including a plurality of engineered structures disposed on a side of the etch stop layer opposite the polymer substrate; a planarizing backfill layer disposed over the plurality of processed structures, the planarizing backfill layer defining a substantially planar major surface of the planarizing backfill layer having a surface roughness Ra, the difference in refractive index between the planarizing backfill layer and the structured layer being at least 0.25 for at least a first wavelength W1 in a range of 400 nm to 2500 nm; a structured film comprising: an adhesive layer disposed on the substantially planar major surface of the planarizing backfill layer and bonding the structured film to the waveguide, the adhesive layer having an average thickness ta, where Ra<ta<(¼)W1; An optical article comprising:

2. 2. The optical article of claim 1, wherein the structured film further comprises an unstructured layer disposed between the etch stop layer and the polymer substrate, the difference in refractive index between the planarizing backfill layer and the unstructured layer being at least 0.2 for at least the first wavelength W1.

3. The optical article of claim 1 , wherein the processed structure is tilted relative to the etch stop layer.

4. The optical article of any one of claims 1 to 3, further comprising a dynamic separation layer disposed between the etch stop layer and the polymer substrate.

5. The optical article according to any one of claims 1 to 3, wherein the average thickness ta is less than 250 nm.

6. The optical article according to any one of claims 1 to 3, wherein the average thickness ta is less than 100 nm.

7. The optical article of any one of claims 1 to 3, wherein the plurality of processed structures comprises a plurality of nanostructures.

8. A polymer substrate; an etch stop layer disposed on the polymer substrate; a structured layer including a plurality of engineered structures disposed on a side of the etch stop layer opposite the polymer substrate, the engineered structures being inclined with respect to the etch stop layer; a planarizing backfill layer disposed over the plurality of processed structures, the planarizing backfill layer defining a substantially planar major surface of the planarizing backfill layer having a surface roughness Ra, the difference in refractive index between the planarizing backfill layer and the structured layer being at least 0.25 for at least a first wavelength W1 in a range of 400 nm to 2500 nm; an adhesive layer disposed on the substantially planar major surface of the planarizing backfill layer and having an average thickness ta, where Ra<ta<(1 / 4)W1; 1. A structured film comprising:

9. 10. The structured film of claim 8, wherein for at least a majority of said modified structures, each modified structure includes a sidewall that defines an exterior angle relative to said etch stop layer in the range of 45 to 85 degrees.

10. 10. The structured film of claim 8, wherein the structured layer comprises a fluoropolymer and the planarizing backfill layer comprises a metal oxide, nitride, or oxynitride.

11. The structured film of any one of claims 8 to 10, wherein the first wavelength W1 is in the range of 400 nm to 700 nm.

12. A waveguide; a structured film disposed on a major surface of the waveguide, an etch stop layer; a structured layer disposed on the etch stop layer and including a plurality of processed structures, the processed structures being inclined with respect to the etch stop layer; a planarizing backfill layer disposed over the plurality of processed structures, the planarizing backfill layer defining a substantially unstructured major surface of the planarizing backfill layer having a surface roughness Ra, the difference in refractive index between the planarizing backfill layer and the structured layer being at least 0.25 for at least a first wavelength W1 in a range of 400 nm to 2500 nm; a structured film comprising: an adhesive layer disposed on the substantially unstructured major surface of the planarizing backfill layer, the adhesive layer bonding the structured film to the major surface of the waveguide, the adhesive layer having an average thickness ta, where Ra<ta<(¼)W1; An optical article comprising:

13. 13. The optical article of claim 12, wherein the surface roughness Ra is less than 20 nm.

14. A polymer substrate; an etch stop layer; a dynamic separation layer disposed between the polymer substrate and the etch stop layer; a structured layer including a plurality of engineered structures disposed on a side of the etch stop layer opposite the dynamic isolation layer; a planarizing backfill layer disposed over the plurality of processed structures, the planarizing backfill layer defining a substantially planar major surface of the planarizing backfill layer having a surface roughness Ra, the difference in refractive index between the planarizing backfill layer and the structured layer being at least 0.25 for at least a first wavelength W1 in a range of 400 nm to 2500 nm; an adhesive layer disposed on the substantially planar major surface of the planarizing backfill layer and having an average thickness, ta, where Ra<ta<(1 / 4)W1; The dynamic release layer is adapted to facilitate separation of the polymeric substrate and the etch stop layer upon activation.

15. 15. The structured film of claim 14, wherein the dynamic release layer is adapted to peel away from the etch stop layer upon activation.